Political Economy of the Agricultural Sector in a Review of Development Studies in Indonesia - Naerul Edwin Kiky Aprianto; Amanah Aida Qur'an (Universitas Ahmad Dahlan, 2021)
During the New Order period, government policy focused on the politics of development in the agricultural sector. The actual result was that the community could directly fulfill food needs independently (self-sufficiency) in the mid-1980s. However, this conducive condition had to end tragically when in the late 1980s and early 1990s, the agricultural economy suffered due to massive protection in the industrial sector and took place through a conglomerate process that laid the foundations of the economy. The history of the agricultural sector during the New Order period can be a precious lesson in building the Indonesian economy. This agricultural sector has been recognized as having an essential role in the national economy, which can be seen from its ability to contribute to the gross domestic product, employment absorption, job creation opportunities, increasing people’s income, and foreign exchange sources. This research uses a descriptive-qualitative approach with a library review design. In this research, it can be concluded that agricultural development in this era seeks to develop sustainable agricultural systems that must improve farmers’ resources and standard of living to be more prosperous. Therefore, the government must formulate a platform or grand strategy of agricultural development policy so that Indonesian farmers do not get caught up in poverty and unemployment